Effects of a polyphenol-rich grape and blueberry extract (Memophenol™) on cognitive function in older adults with mild cognitive impairment: A randomized, double-blind, placebo-controlled study - Lopresti, Adrian L.; Smith, Stephen J.; Pouchieu, Camille; Pourtau, Line; Gaudout, David; Pallet, Véronique; Drummond, Peter D. (Frontiers in Psychology, 2023)
BACKGROUND: Polyphenols are naturally-occurring organic compounds found in plants. Research suggests that their intake reduces the risk of cognitive decline and related dementias. Grapes and blueberries are polyphenol-rich foods that have attracted attention for their potential cognitive-enhancing effects. PURPOSE: Examine the effects of supplementation with a standardized and patented polyphenol-rich grape and blueberry extract (MemophenolTM) on cognitive function in older adults with mild cognitive impairment. STUDY DESIGN: Two-arm, 6-month, parallel-group, randomized, double-blind, placebo-controlled trial. METHODS: One hundred and forty-three volunteers aged 60 to 80 years with mild cognitive impairment were supplemented with either 150 mg of MemophenolTM, twice daily or a placebo. Outcome measures included computer-based cognitive tasks, the Behavior Rating Inventory of Executive Function (BRIEF-A), the Cognitive Failures Questionnaire, and the CASP-19. RESULTS: Compared to the placebo, MemophenolTM supplementation was associated with greater improvements in the speed of information processing (p = 0.020), visuospatial learning (p = 0.012), and the BRIEF-A global score (p = .046). However, there were no other statistically-significant between-group differences in the performance of other assessed cognitive tests or self-report questionnaires. MemophenolTM supplementation was well-tolerated with no reports of significant adverse reactions. CONCLUSIONS: The promising results from this trial suggest that 6-months of supplementation with MemophenolTM may improve aspects of cognitive function in adults with mild cognitive impairment. Further research will be important to expand on the current findings and identify the potential mechanisms of action associated with the intake of this polyphenol-rich extract.